Pertanggungjawaban Hukum Notaris Terhadap Pemalsuan Pembuatan Akta Pernyataan Keputusan Rapat Umum Pemegang Saham Luar Biasa (Studi Putusan No. 898/Pid.B/2022/PN.Jkt.Brt) - Purba, Sarah Putri F; Purba, Hasim; S, Suprayitno (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The problems studied in this study are how the Notary's Legal Responsibility for Forgery of the Making of the Deed of Statement of the GMS Decision, what are the Legal Consequences of Forgery of the Making of the Deed of Statement of the GMS Decision Made by a Notary and what are the Considerations of the District Court Judge in the Decision of Case Number: 898 / Pid.B / 2022 / PN.Jkt.Brt. The method used in this study is normative juridical or library legal research which can be interpreted as legal research by examining library materials and secondary materials. The nature used in this study is descriptive-analytical. The data collection technique used in this study is through literature study. The data collection tool used in this study is document study, which includes legislation and other documents directly related to the problems discussed. The data obtained will be analyzed qualitatively and conclusions drawn deductively. The results of this study explain that the elements of the crime of forgery of a deed then deliberate/negligent error that the notary made the deed intentionally or knowingly or desired the result is that the deed is aware that the deed violates the formal aspects of making a notarial deed and the making of the deed is based on the will of the notary because the documents listed in the deed are fake documents and the related party denies the existence of the deed. Legal Consequences of Forgery of Making a Deed of Statement of the Decision of the Extraordinary GMS Made by a Notary are that the notary is sentenced to a criminal penalty with the offense of forgery of Article 266 paragraph (1) of the Criminal Code in conjunction with Article 56 paragraph (1) of the Criminal Code. Analysis of the Judge's Decision Considerations of the District Court Judge in the Decision of Case Number: 898/Pid.B/2022/PN.Jkt.But is that the Defendant has committed an act of forgery of a deed and sentenced the Defendant to submit to this decision.